Fostering Zero Waste Communities: A Participatory Action Research Approach to Implementing 3R Principles in a Suburban Indonesian Village - Suroto S; Vega Candra Dinata; Fifukha Dwi Khory; Bayu Budi Prakoso (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2026)
Addressing Indonesia's national target of 30% waste reduction by 2025, this study tackles the conventional